ENVIR IONMENTAL ISSUES OF COMPETITIVENESS OF RUSSIAN MULTINATIONAL OIL AND GAS CORPORATIONS IN LIQUEFIED NATURAL GAS MARKETS - N. A. Piskulova; M. V. Babaeva (Модернизация, инновация, развитие)
Owing to tough state environmental management requirements and ecological regulations, oil and gas multinational corporations (MNC) make more and more attempts to mitigate negative environmental impacts resulting from their industrial activities, their competitiveness beingstrengthened therewith. The use of liquefied natural gas (LNG) is associated with less environmental impact in comparison with oil and coal, particularly so far as the hotbed effect is concerned. In the field of innovative technological development, Russian MNC drag so far well behind most advanced western corporations who provide for less negative impact of their production activities upon environment.